Investigating In Disclosure Of Carbon Emissions: Influencing The Elements Using Panel Data - Imam Hidayat; Tubagus Ismail; Muhamad Taqi; Agus Solikhan Yulianto (Universitas Muhammadiyah Malang, 2022)
This study aims to examine the effect of media exposure, environmental performance, profitability, company size on disclosure of carbon emissions. The research population includes all companies on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sample in the study was determined by purposive sampling technique and 18 companies were found over a period of 5 years, resulting in 90 research samples. The analytical method used is Panel Data Regression Analysis. The results of the study show that media exposure, environmental performance and company size have a positive effect on disclosure of carbon emissions, while profitability has no effect on disclosure of carbon emissions. The limitation of this research is that this research only focuses on manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX), so that it cannot describe the condition of the population of all companies in Indonesia so that it can provide different results if carried out in different industries. The results of this study are expected to pay more attention to the company's environmental impact by increasing disclosure of environmental information related to greenhouse gas emissions because it can be added value to the company for stakeholders or investors.